Constitutive LH receptor activity impairs NO-mediated penile smooth muscle relaxation. Issue 1 (January 2021) - Hiremath, Deepak S; Priviero, Fernanda B M; Webb, R Clinton; Ko, CheMyong; Narayan, Prema
Abstract : Timely activation of the luteinizing hormone receptor (LHCGR) is critical for fertility. Activating mutations in LHCGR cause familial male-limited precocious puberty (FMPP) due to premature synthesis of testosterone. A mouse model of FMPP (KiLHR D582G ), expressing a constitutively activating mutation in LHCGR, was previously developed in our laboratory. KiLHR D582G mice became progressively infertile due to sexual dysfunction and exhibited smooth muscle loss and chondrocyte accumulation in the penis. In this study, we tested the hypothesis that KiLHR D582G mice had erectile dysfunction due to impaired smooth muscle function. Apomorphine-induced erection studies determined that KiLHR D582G mice had erectile dysfunction. Penile smooth muscle and endothelial function were assessed using penile cavernosal strips. Penile endothelial cell content was not changed in KiLHR D582G mice. The maximal relaxation response to acetylcholine and the nitric oxide donor, sodium nitroprusside, was significantly reduced in KiLHR D582G mice indicating an impairment in the nitric oxide (NO)-mediated signaling. Cyclic GMP (cGMP) levels were significantly reduced in KiLHR D582G mice in response to acetylcholine, sodium nitroprusside and the soluble guanylate cyclase stimulator, BAY 41-2272. Expression of NOS1, NOS3 and PKRG1 were unchanged. The Rho-kinase signaling pathway for smooth muscle contraction was not altered. Together, these data indicate that KiLHR D582G mice have erectile dysfunction due to impaired NO-mediated activation of soluble guanylate cyclase resulting in decreased levels of cGMP and penile smooth muscle relaxation. These studies in the KiLHR D582G mice demonstrate that activating mutations in the mouse LHCGR cause erectile dysfunction due to impairment of the NO-mediated signaling pathway in the penile smooth muscle.